Lugar Marcado: uma série em formato podcast sobre nation branding - Oliveira, João Ricardo Bezerra Vasconcelos de (2023)
In an increasingly competitive scenery, it is essential for organizations to have a distinguishing factor that makes them more appealing to their diverse audiences. The concept of differentiation is crucial, and this extends beyond the business sphere; countries also benefit from the advantages provided by a positive brand image. It is in this context that "nation branding" emerges, a management strategy that adapts branding perspectives to promote and strengthen a country's image with the aim of generating institutional gains for them. Aspects such as a country's culture and identity, promoted internationally through media products within the framework of a cultural expansion strategy, are some of the methods used to propagate a country's image abroad. It is within this context that the proposed product, the pilot episode of the "Lugar Marcado" podcast, was developed with the goal of fostering a discussion in the auditory media, and in the Portuguese language, about the impact of these activities on a country's image, as well as their ability to generate soft power, resulting in tangible and intangible benefits for nations. These benefits manifest in the signing of international trade agreements, increased tourism, the attraction of a specialized labor force, and other areas that help enhance the economic possibilities of these countries. Through the "Lugar Marcado" podcast, we aim to explore the intersection between Nation Branding and its economic, cultural, and political implications through theoretical discussions on the subject and case analyses of countries with successful brand management strategies.